Area Modification in Constructed Public Buildings in An Adaptive Reuse Perspective Former Presidency of Mosul University as a Case study - Abdullah, Firas H.; AlAllaf, Emad H. (Sulaimani Journal for Engineering Sciences, 2019)
The construction sector has recently rehabilitated and adapted a large number of buildings designed to meet the humanitarian needs and provide space required for various activities and services, that achieve the objectives of economic, cultural, technical and demographic changes. The Adaptive Reuse is one of the vital methods to provide buildings, due to their economic advantages in saving energy, resources, efforts and costs by maintaining constructed buildings. The paper discusses the importance of the constructed buildings and their physical and moral values, which determine the economic feasibility to prolong the building life. It also clarifies the contradictory relationship between building functional and structural age, beside t he internal and external challenges faced by buildings which represented by changes in space requirements, as well as physical, technical, social and economic changes. It deals with the adaptive reuse concept as a mechanism for retaining the socially required buildings, then determining the elements of this technique, applying what was drawn on a case study - a public construction (the previous presidency building of the Mosul University) which has been emptied of its function to occupy a new one (a guesthouse for the campus), measuring the efficiency of alternatives design, and determining the economic optimization based on the possibilities of spatial modification within adaptive principles and flexible design ideas. Following by presenting a set of recommendations to adopt in reusing process for altering the characteristics of an abandoned building by changing its function. The study analyzed the proposed building, its design and construction characteristics, evaluated them according to the principles of flexible design ideas as effective factors in adapting the building to the new use. Then, it presented a set of design alternatives that were implemented according to adaptability strategies, and next performing a comparison on the economic and functional characteristics - with neutralizing the aesthetic values - which are carried by each of these alternatives, which achieving the functional program derived from the analysis of a set of international models of university guesthouses, especially those meeting the local needs, followed by realizing the comparisons results, conclusions and recommendations for the project.
Keywords: Adaptive Reuse; Area Modification; Constructed Buildings; Former Presidency Building of Mosul University